Diferencias en algunos parámetros demográficos de Oryzomys chapmani (Rodentia: Muridae) asociadas a tres estados sucesionales de bosque mesófilo de montaña en Oaxaca, México - Santos-Moreno, Antonio; Briones-Salas, Miguel Ángel; López-Wilchis, Ricardo (Instituto de Ecología, A.C., 2007)
We studied the differences among apparent survival and capture probabilities, sex ratio, and population size of the Mexican endemic rodent Oryzomys chapmani associated to a chronosequence integrated by three succesional stages of cloud forest. The study was made at the Sierra Norte de Oaxaca region, and the regeneration times of the forests studied were 15 (Young), 40 (Medium), and 100 (Mature) years. 227 adult specimens were capture, marked, and released by 14 months. The apparent survival probabilities were similar in the Young and Medium forests, without fluctuations across time, whereas in the Mature Forest the dry season shows higher value. The capture probabilities did not show variation across time in the Young and Medium forests, but in the Mature Forest showed difference, with higher value in the rainy season. The Young Forest shows a significant excess of males, whereas the Medium and Mature Forest do not differ significantly from the 1:1 sex ratio. The population size was from 42 individuals by hectares in the rainy season to 302 in the dry season, both in the Mature Forest.